Conflicting Discourses: Navigating the Tensions of Becoming a Literacy Coach. Issue 4 (2nd October 2017) - MacPhee, Deborah; Jewett, Pamela
ABSTRACT: During recent years, literacy coaching has become a widespread model of professional development for teachers in schools across the United States. However, there is a shortage of research and policy to inform the preparation and ongoing work of literacy coaches. In this article, the researchers use a modified version of Gee's identity framework to examine teachers' reflective writing as they learned about and practiced coaching in one school district. Findings show that teachers invoked multiple conflicting discourses of coaching that contributed to tensions in their work. The researchers argue that such tensions can stand in the way of educators constructing coaching identities that allow them to support and sustain meaningful professional development for teachers.